2022
DOI: 10.1039/d1py01412a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and depolymerization of self-immolative poly(disulfide)s with saturated aliphatic backbones

Abstract: Self-immolative polymers (SIPs) are a class of degradable stimuli-responsive polymers, which, upon removal of labile end-caps, depolymerize selectively and stepwise to small molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Recently, we published that poly(dithiothreitol) (pDTT) with pendant anthraquinone (AQ) groups exhibited complete depolymerization in response to electrochemical reduction of AQ to AQ• − in what was the first use of electrochemically induced depolymerization triggering of SIPs [ 29 ]. Alternatively, dithiothreitol and base (triethylamine) can be used to initiate depolymerization [ 29 , 30 , 31 , 32 ]. An interesting aspect of the indirect electron transfer (or redox catalysis) [ 33 , 34 , 35 ] approach for carrying out reduction processes involving bond fragmentation is that it can lower significantly the electrochemical potential needed for accomplishing the process, and in a very controlled fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we published that poly(dithiothreitol) (pDTT) with pendant anthraquinone (AQ) groups exhibited complete depolymerization in response to electrochemical reduction of AQ to AQ• − in what was the first use of electrochemically induced depolymerization triggering of SIPs [ 29 ]. Alternatively, dithiothreitol and base (triethylamine) can be used to initiate depolymerization [ 29 , 30 , 31 , 32 ]. An interesting aspect of the indirect electron transfer (or redox catalysis) [ 33 , 34 , 35 ] approach for carrying out reduction processes involving bond fragmentation is that it can lower significantly the electrochemical potential needed for accomplishing the process, and in a very controlled fashion.…”
Section: Introductionmentioning
confidence: 99%
“…40 Furthermore, they investigated a broader range of nonfunctionalized poly(disulfide)s, prepared from monomers such as 1,4-butanedithiol, 1,5-pentanedithiol, and 1,6-hexanedithiol, to obtain poly(disulfide)s with different alkyl chain lengths. 41 The results indicated that poly(1,4-butanedithiol) and poly-(1,5-pentanedithiol) undergo head-to-tail cyclization elimination upon end-capping removal, although poly(1,5-pentanedithiol) exhibited a significantly slower degradation rate. This difference arises from the higher thermodynamic stability of the six-membered ring 1,2-dithiane produced during the degradation of poly(1,4-butanedithiol) compared to the seven-membered ring 1,2-dithiepane released during the degradation of poly (1,5-pentanedithiol).…”
Section: Architecture Of Sipmentioning
confidence: 97%
“…Furthermore, by modifying the molecular architecture, the addition of specific compounds to trigger the depolymerization via abiotic and biotic methods is being considered. [70][71][72][73]77] The concept of self-immolative polymers referring to polymers that are designed and programmed to disassemble through a dominolike effect in response to an external stimuli has been explored. [90] The biodegradation could be accelerated by designing and adding compounds that trigger depolymerization in specific environments and conditions (Figure 7).…”
Section: Incorporation Of Additives During Processingmentioning
confidence: 99%